Sejarah Walisongo Dalam Mengembangkan Ajaran Islam di Indonesia - Hidayah, Rahma; Rahmadani, Rifa Amelia; D, Demina; Alzami, Yahya (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Walisongo is a person who spread Islam on the island of Java. Walisongo simply means lovers of Allah who number as many as nine people, in the era of development now many children do not know the name Walisongo because many children are now bored learning about the history of Islamic culture that is very boring Walisongo, this aims to educate children so that children now know the development of teachings taught by Walisongo because it can expand a child's insight and can be used as a lesson and motivation about how Walisongo's struggle in developing teachings Indonesians about Walisongo and have the talent and desire to know the history of Islamic culture including the history of the spread of Islam on the island of Java developed by Walisongo. The method used in this research is a qualitative method because because the qualitative method can explain comprehensively and clearly about the spread of Islam in Java put forward by Walisongo and can ask ask the opinion of the informants or people who are experts in the field of respondents. This can be done by conducting observations to schools. The result of this research is that Walisongo is the guardian who developed and spread the teachings of Islam on the island of Java, Walisongo numbers as many as nine people, this guardian can spread the teachings of Islam, although started from the island of Java, but still, the spirit of Islamic teachings. developing throughout the islands in Indonesia, the conclusion is that Islamic teachings are very useful for today, because nowadays children do not know about the history of the entry of Islam in Indonesia and the spread of Islamic teachings.